Problem of the formation of the theoretical foundations of the development of the volunteer movement in sports (an integral component of the industry of the regulatory framework of sports law) - Саннікова, Марина; Петренко, Ірина (Slobozhanskyi Herald of Science and Sport, 2019)
Marina Sannikova & Iryna Petrenko Purpose: to substantiate the defining provisions of the optimization of organizational and methodological activities in the process of preparing volunteers in the system of sports competitions and managing this process. Material & Methods: in the conducted research were used: the analysis of literary sources and regulatory documents relating to the problem under consideration; expert assessments; modeling of organizational processes; method of chronological observations; methods of subjective diagnosis of behavior motivation, mathematical modeling in the processing of empirical data. Results: the meaningful meaning of the basic concepts used in the volunteer movement in question was established, the mechanism for forming volunteering as a phenomenon in the structure of interdependent social relations was established, methods for classifying the qualitative characteristics of volunteer activity and the quantitative expression of their manifestation were developed. Conclusions: the problem of forming the theoretical foundations of the development of the volunteer movement in sports reaches its solvability due to the developed methods of geometric expression of the semantic content of the terms and triads used, which are the basis of the construction of special semantic spaces.